Nanopore structures of isolated kerogen and bulk shale in Bakken Formation - Liu, K.; Ostadhassan, M.; Zou, J.; Gentzis, T.; Rezaee, M. Reza; Bubach, B.; Carvajal-Ortiz, H. (Elsevier Ltd, 2018)
Pores that exist within the organic matter can affect the total pore system of bulk shale samples and, as a result, need to be studied and analyzed carefully. In this study, samples from the Bakken Formation, in conjunction with the kerogen that was isolated from them, were studied and compared through a set of analytical techniques: X-ray diffraction (XRD), Rock-Eval pyrolysis, Fourier Transform infrared spectroscopy (FTIR), and gas adsorption (CO 2 and N 2 ). The results can be summarized as follows: 1) quartz and clays are two major minerals in the Bakken samples; 2) the samples have rich organic matter content with TOC greater than 10 wt%; 3) kerogen is marine type II; 4) gas adsorption showed that isolated kerogen compared to the bulk sample has larger micropore volume and surface area, meso- and macropore volume, and Brunauer–Emmett–Teller (BET) surface area; 5) deconvolution of pore size distribution (PSD) curves demonstrated that pores in the isolated kerogen could be separated into five distinct clusters, whereas bulk shale samples exhibited one additional pore cluster with an average pore size of 4 nm hosted in the minerals. The comparison of PSD curves obtained from isolated kerogen and bulk shale samples proved that most of the micropores in the shale are hosted within the organic matter while the mesopores with a size ranging between 2 and 10 nm are mainly hosted by minerals. The overall results demonstrated that organic matter-hosted pores make a significant contribution to the total porosity of the Bakken shale samples.